(untitled) (Research, Society and Development, 2021)
The tobacco can generate chemical addiction to its users, especially in vulnerable groups such as university students which upon entering university may develop conflicts of principles employed by family education, besides the need for social insertion and the influence of friends The purpose of this study is the analysis of the biopsychosocial aspects related to tobacco consumption among college students. To reach this objective, an integrative literature review was carried out using the SciELO Brasil, SciELO Saúde Pública, SciElo, OneFile and Scopus databases. Using the terms "aspectos biopsicossociais", "consumo de produtos derivados do tabaco", "consumo de tabaco", "tabagismo", "estudante universitário". The inclusion and exclusion criteria were observed on 3.105 articles in which ten of them made up the final sample. It was observed that college students are vulnerable to tobacco use due to factors such as social influence, psychological pressure, and anxious situations generated by the university. Tobacco consumption by young people is marked by the use of other drugs, usually alcohol, causing harm to health. It is concluded that health students are more active in this consumption, despite knowing the risks caused by tobacco.